Patterns and Determinants of Essential and Toxic Elements in Chinese Women at Mid-Pregnancy, Late Pregnancy, and Lactation - Zhou, Yubo (Nutrients, 2021)
Maternal status of essential and toxic elements affects the health of the mother, developing fetus, or breastfeeding infant. However, few studies have examined the patterns of these elements and their determinants in pregnant or lactating women. Plasma samples of 1211 healthy mid-pregnant, late pregnant, and lactating women enrolled in coastland, lakeland, and inland areas of China from May–July 2014, were analyzed for concentrations of 15 elements, using inductively coupled plasma mass spectrometry. The adjusted median concentrations of elements varied by physiologic stage and region. Lactating versus pregnant women showed higher concentrations of Zn, Cr, Mo, Ni, Sb, Cd and Pb, but lower concentrations of Cu, I, Al and Hg. In pregnant women, the concentrations of Fe, Zn, I, Mo, Ni, Al, Hg and Cd were higher in mid- versus late-pregnancy. Overall, the highest concentrations were observed in Zn, I, Mn, Al, and Pb in coastland, in Hg in lakeland, and in Fe in inland area. Element concentrations varied by maternal age, pre-pregnancy BMI, education, parity, delivery mode, feeding practice, and intakes of aquatic products and mutton. In conclusion, essential and toxic elements coexisted in pregnant and lactating women, and their concentrations varied by physiologic stages, regions, maternal socio-demographic characteristics and dietary factors.